Plasma 1-carbon metabolites and academic achievement in 15-yr-old adolescents - Nilsson, Torbjörn K; Hurtig-Wennlöf, Anita; Sjöström, Michael; Herrmann, Wolfgang; Obeid, Rima; Owen, Jennifer R; Zeisel, Steven (The FASEB journal, 2016)
Academic achievement in adolescents is correlated with 1-carbon metabolism (1-CM), as folate intake is positively related and total plasma homocysteine (tHcy) negatively related to academic success. Because another 1-CM nutrient, choline is essential for fetal neurocognitive development, we hypothesized that choline and betaine could also be positively related to academic achievement in adolescents. In a sample of 15-yr-old children (n= 324), we measured plasma concentrations of homocysteine, choline, and betaine and genotyped them for 2 polymorphisms with effects on 1-CM, methylenetetrahydrofolate reductase (MTHFR) 677C>T, rs1801133, and phosphatidylethanolamineN-methyltransferase (PEMT), rs12325817 (G>C). The sum of school grades in 17 major subjects was used as an outcome measure for academic achievement. Lifestyle and family socioeconomic status (SES) data were obtained from questionnaires. Plasma choline was significantly and positively associated with academic achievement independent of SES factors (paternal education and income, maternal education and income, smoking, school) and of folate intake (P= 0.009,R(2)= 0.285). With the addition of thePEMTrs12325817 polymorphism, the association value was only marginally changed. Plasma betaine concentration, tHcy, and theMTHFR677C>T polymorphism did not affect academic achievement in any tested model involving choline. Dietary intake of choline is marginal in many adolescents and may be a public health concern.-Nilsson, T. K., Hurtig-Wennlöf, A., Sjöström, M., Herrmann, W., Obeid, R., Owen, J. R., Zeisel, S. Plasma 1-carbon metabolites and academic achievement in 15-yr-old adolescents.